Ureteral obstruction by an aberrant renal artery: A case report (Indian Journal of Case Reports, 2018)
The ureter is a muscular tubular structure that carries urine from the kidney to the urinary bladder. It is usually about 20–25 cm in length and 3–5 mm diameter. The upper half lies in the belly and the lower half in the pelvic area. A ureteral obstruction is a blockage of either unilateral or bilateral ureters that carry urine from the kidneys to the urinary bladder. Ureteral obstruction can be curable. However, if it is not treated, symptoms can quickly move from mild pain, fever, and infection to severe including loss of kidney function, sepsis, and death. Here, we report the case of an upper ureteral obstruction by an aberrant artery. The artery was originating from the right renal artery, supplying the right psoas muscle, and causing gross proximal hydroureteronephrosis in a 24-year-old male patient. The patient was diagnosed using contrast-enhanced computed tomography through the abdomen examination.